Expression and contributions of the Kir2.1 inward-rectifier K+ channel to proliferation, migration and chemotaxis of microglia in unstimulated and anti-inflammatory states - Lam, Doris; Schlichter, Lyanne C. (Frontiers in Cellular Neuroscience, 2015)
When microglia respond to CNS damage, they can range from pro-inflammatory (classical, M1) to anti-inflammatory, alternative (M2) and acquired deactivation states. It is important to determine how microglial functions are affected by these activation states, and to identify molecules that regulate their behavior. Microglial proliferation and migration are crucial during development and following damage in the adult, and both functions are Ca2+-dependent. In many cell types, the membrane potential and driving force for Ca2+ influx are regulated by inward-rectifier K+ channels, including Kir2.1, which is prevalent in microglia. However, it is not known whether Kir2.1 expression and contributions are altered in anti-inflammatory states. We tested the hypothesis that Kir2.1 contributes to Ca2+ entry, proliferation and migration of rat microglia. Kir2.1 (KCNJ2) transcript expression, current amplitude, and proliferation were comparable in unstimulated microglia and following alternative activation (IL-4 stimulated) and acquired deactivation (IL-10 stimulated). To examine functional roles of Kir2.1 in microglia, we first determined that ML133 was more effective than the commonly used blocker, Ba2+; i.e., ML133 was potent (IC50=3.5 M) and voltage independent. Both blockers slightly increased proliferation in unstimulated or IL-4 (but not IL-10)-stimulated microglia. Stimulation with IL-4 or IL-10 increased migration and ATP-induced chemotaxis, and blocking Kir2.1 greatly reduced both but ML133 was more effective. In all three activation states, blocking Kir2.1 with ML133 dramatically reduced Ca2+ influx through Ca2+-release-activated Ca2+ (CRAC) channels. Thus, Kir2.1 channel activity is necessary for microglial Ca2+ signaling and migration under resting and anti-inflammatory states but the channel weakly inhibits proliferation.